Sluice Box Sebagai Alternatif Pengganti pada Pengolahan Emas Menggunakan Merkuri pada Penambangan Emas Skala Kecil di Distrik Uwapa Kampung Gamey Biru Kabupaten Nabire Provinsi Papua Tengah - Detevince Butu; Endang Hartiningsih; Rahmat Indrajati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
People's mining activities in Gamey Village, Uwapa District, Nabire Regency, Central Papua Province are carried out to meet daily needs and improve the welfare of the local community. This mining activity is based on alluvial deposit conditions and is applied for mining sediments on the surface and using alcon machines. for high pressure water spray. This community mining activity is divided into several stages starting from preparation of mining land, processing and production processes as well as selling gold products for sale. This research aims to examine the gold processing used by small-scale miners in Uwapa District, Gamey Village, and its impact on the environment and public health. The main focus of this research is on the use of the sluice box method, which is the gold processing technique most commonly used by local communities. This method was chosen for its simplicity and low cost, although the gold recovery efficiency varies between 50-70%. Additionally, this research evaluates alternative technologies such as shake tables and centrifuges that can increase gold recovery efficiency and be more environmentally friendly. The research results show that the implementation of alternative technology requires training, procurement of adequate equipment and infrastructure as well as ongoing monitoring. By adopting better technology, it is hoped that gold mining activities in Gamey Village can run more productively and sustainably, improving community welfare without damaging the environment.